Robiquetia ormerodii (Orchidaceae; Epidendroideae), a new species from the islands of Visayas, Philippines. Issue 1 (2nd January 2019) - Naive, Mark Arcebal K.; Dalisay, Jade Ann Grace P.; Alejandro, Grecebio Jonathan D.
ABSTRACT: Robiquetia ormerodii (Orchidaceae; Epidendroideae; Vandeae; Aeridinae) Naive, Dalisay & Alejandro, a new endemic species from Visayas, Philippines, is herein described and illustrated. It is comparable to R. micramphora by having a yellow flower with spots, however, it differs significantly in having a labellum with oblong side lobes, strongly curved spur, column with big red margin and longer verrucose rostellum. With this discovery, the Philippines now houses a total number of 20 species of Robiquetia, of which 18 are known to be endemic.